The Inevitability of Caregiving Jobs: COVID Crisis as a Reflection of Social and Legislative Limitations in the Domestic Sector - Díaz Gorfinkiel, Magdalena; Elizalde-San Miguel, Begoña (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
This article presents an analysis of the household employment sector during 2020, taking into account the consequences experienced during the socio-sanitary crisis of COVID together with the traditional precariousness of this economic field. The main aim is to examine the relation between the concrete measures taken during the socio-sanitary crisis and the structural forms of assessment and operation of this sector. To do this, the evolution of hiring in this sector during the first months of the pandemic is analyzed, as well as the legislative and socio-sanitary protection initiatives implemented for workers in this labour field. Despite their relevance, the measures adopted by the public administrations were late and incomplete, causing a progressive repositioning of care on the margins of social priorities.
Keywords: COVID-19; domestic sector; care activities; social and labour protection